Improving performances of ITO/GaP contact on AlGaInP light-emitting diodes - 李春伟 朱彦旭 沈光地 张勇辉 秦园 高伟 蒋文静 邹德恕 (Chinese physics B, 2010)
In this paper AlGaInP light emitting diodes with different types of electrodes： Au/Zn/Au-ITO Au/Ti-ITO Au/Ge/Ni-ITO and Au-ITO are fabricated. The photoelectricity properties of those LEDs are studied. The results show that the Au/Zn/Au electrode greatly improves the performance of LEDs compared with the other electrodes. Because the Au/Zn/Au electrode not only forms a good Ohmic contact with indium tin oxide （ITO）, but also reduces the specific contact resistances between ITO and GaP, which are 1.273× 10^-6 Ω·cm^2 and 1.743× 10^-3 Ω·cm^2 between Au/Zn/Au-ITO and ITO-GaP respectively. Furthermore, the textured Zn/Au-ITO/Zn electrode is designed to improve the performances of LEDs, reduce the forward-voltage of the LED from 1.93 to 1.88 V, and increase the luminous intensity of the LEDs from 126 to 134 mcd when driven at 20 mA.